Scale for measurement of healthcare-associated infection risk in adult patients : development and content validation (2019)
ABSTRACT: Introduction: Hospital settings involve several risk factors related to healthcare-associated infections (HAIs). A method that contributes to prevention and control is identification of risks to enable implementation of preventative measures. It is believed that this identification can be accomplished using scales. The present study attempts to develop and validate the face and content of a new scale for measuring HAIs risk in hospitalized adults. Materials and Methods: A methodological study conducted to develop and validate the face and content of the Adult Inpatients Infection Risk Assessment scale, which underwent evaluation by a committee of 23 experts with experience in HAIs. The scale’s validity was tested using the Content Validity Index (CVI). Results: 15 items were retained in the scale, grouped into two dimensions: intrinsic and extrinsic factors. Certain minor adjustments were needed to improve the clarity of some items. Items’ CVIs ranged from 0.83 to 1.0 and the scale’s mean CVI was 0.90. Discussion: The Adult Inpatients Infection Risk Assessment scale can be used as a technology of low cost for the measurement of the risk of infection, which allows the planning of more accurate and organized interventions of the health team targeting at preventive and safe care during hospitalization. Conclusions: The findings supported the face and content validity of the Adult Inpatients Infection Risk Assessment Scale